2021
DOI: 10.1002/hed.26771
|View full text |Cite
|
Sign up to set email alerts
|

A matched pair analysis of oncological outcomes in human papillomavirus‐negative oropharyngeal squamous cell carcinoma: Transoral surgery versus radiotherapy or concurrent chemoradiation

Abstract: Background With the termination of RTOG 1221, there remains a lacuna regarding the optimal treatment for human papillomavirus (HPV)‐negative oropharyngeal squamous cell carcinoma (OPSCC). Methods Matched pair analysis with propensity score matching (PSM) between Arm I (transoral surgery [TOS] + risk‐stratified adjuvant treatment) and Arm II (nonsurgical treatment − radiation/chemoradiation) in HPV(−) OPSCC. Results Unmatched comparison of Arm I (n = 57) and Arm II (n = 89) indicated significantly better overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…48 For oncologic results of stage III-IV patients treated with TORS, it can be found that compared with CRT, the survival results obtained by primary treatment with TORS and the adjuvant therapy under the condition of detailed pathological staging are more encoraging. [48][49][50] In our cohort, the survival rates of 58 patients with HPV-negative OPSCC were not statistically different from those of the HPV-positive group. The results presented in our study and previous findings suggested that HPV-negative patients might benefit from TORS.…”
Section: Follow-up and Survival Outcomescontrasting
confidence: 48%
See 1 more Smart Citation
“…48 For oncologic results of stage III-IV patients treated with TORS, it can be found that compared with CRT, the survival results obtained by primary treatment with TORS and the adjuvant therapy under the condition of detailed pathological staging are more encoraging. [48][49][50] In our cohort, the survival rates of 58 patients with HPV-negative OPSCC were not statistically different from those of the HPV-positive group. The results presented in our study and previous findings suggested that HPV-negative patients might benefit from TORS.…”
Section: Follow-up and Survival Outcomescontrasting
confidence: 48%
“…Recently, an analysis based on the National Cancer Data Base (NCDB) and Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2016 support the frontline surgery in patients with T1‐2N1‐2bM0 HPV‐negative oropharyngeal cancer, which had improved OS as compared with the group who received CRT (5‐year OS: 74.0% vs 62.9%, P = .012) 48 . For oncologic results of stage III‐IV patients treated with TORS, it can be found that compared with CRT, the survival results obtained by primary treatment with TORS and the adjuvant therapy under the condition of detailed pathological staging are more encoraging 48–50 . In our cohort, the survival rates of 58 patients with HPV‐negative OPSCC were not statistically different from those of the HPV‐positive group.…”
Section: Discussionmentioning
confidence: 99%
“…Upon closer inspection, for the majority of these studies the TOS and primary RT group are unbalanced, with the TOS group having patients with earlier T and N classi cation disease on average (7,8).This surgical bias is rarely acknowledged in these manuscripts as a potential confounder. Some groups have carried out a case-control matching, such as an analysis of the National Cancer Database by Thakar and colleagues, which demonstrated superior survival outcomes for patients undergoing TORS over RT (n = 1698) (22), but this study still did not control for surgical resectability. Our work herein has highlighted that even if TOS and RT groups were matched for T and N classi cation, there is still an inherent bias of the patients that are selected for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…RTOG 1221 was a prospective, randomized, control trial that aimed to compare TOS vs. primary (chemo)radiation for T1 -T2, N0 -N2b, HPV-negative OPSCC (24), and ORATOR 3 (NCT04220749) was a randomized trial with a very similar study schema, and both closed due to poor patients recruitment. Given the declining rates of HPVnegative OPSCC (22), and the failed accrual of these two studies, it is unlikely such a trial is possible. If a randomized controlled trial was attempted again, broad international participation would be critical.…”
Section: Discussionmentioning
confidence: 99%